Development and Psychometric Testing of the Nurses’ Professional Dignity Scale - Michela Piredda; Maddalena De Maria; Rosario Caruso; Anna Marchetti; Giorgia Petrucci; Anna Cerra; Joyce J. Fitzpatrick; Alessandro Stievano (Nursing Reports)
Background/Objectives: Human dignity is an inalienable value central to human rights and ethics. Professional dignity is pivotal to fostering self-esteem, job satisfaction, and high-quality care in nursing. Despite its importance, no validated tool currently exists to measure nurses’ professional dignity in English-speaking contexts. This study aimed to develop and psychometrically test the Nurses’ Professional Dignity Scale (NPDS). Methods: The tool’s development was guided by a theoretical model from a meta-synthesis. A consensus meeting with five nurse researchers identified three core dimensions for the NPDS: Respect, Professional Value, and Appreciation. Nineteen items were initially generated and refined through face and content validity assessments (all item-level content validity indices [I-CVIs] ≥ 0.80; scale-level content validity index/Ave [S-CVI/Ave] = 0.92). Psychometric testing was conducted with 227 nurses across clinical settings in the United States using confirmatory factor analysis (CFA) to validate a three-factor model. Results: The CFA confirmed the three-factor model with acceptable fit indices (CFI = 0.938, TLI = 0.923, RMSEA = 0.069), resulting in the retention of 15 items. The scale demonstrated excellent reliability, with composite reliability coefficients of 0.92 for Respect, 0.82 for Professional Value, 0.93 for Appreciation, and 0.91 for the overall scale. Conclusions: The NPDS is a valid and reliable measure of nurses’ professional dignity, aligning with theoretical frameworks. It captures both status-dignity and condition-dignity aspects, encompassing respect, professional competence, and societal appreciation, offering a multidimensional structure for assessing individual domains and overall scores. The NPDS contributes to advancing nursing research and practice by addressing workplace dignity, enhancing job satisfaction, and fostering supportive organizational environments that recognize nurses’ professional worth. Future studies are recommended to validate the scale in diverse populations and explore its stability over time through longitudinal research. This study highlights the importance of preserving nurses’ dignity in improving professional identity, workplace environments, and patient care outcomes.